2011
DOI: 10.1016/j.etp.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential immunotoxicity of histone deacetylase inhibitors on malignant and naïve hepatocytes

Abstract: Western blot analysis showed that all HDIs studied downregulated the anti-apoptotic protein cFLIP, but only VPA additionally affected the expression level of XIAP. Furthermore, in models of the intrinsic apoptosis pathway, i.e. in HepG2 cells treated with Melphalan and in primary hepatocytes irradiated with UV light, only VPA exhibited significant sensitisation.These findings extend the biochemical, pharmacological and toxicological basis for HDI therapy and provide a caveat for clinical use in patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Deacetylation is mediated by histone deacetylase (HDAC), which catalyzes the removal of acetyl functional group from the N‐terminal tails of histone proteins, resulting in a more compact chromatin structure and represses gene transcription. Previous studies have indicated that the higher expression of HDACs is associated with tumor cell proliferation, differentiation, invasion, and metastasis and is highly correlated to poor prognosis and survival rate 4,5 . HDACs are involved in gene regulations, stress resistance, and tumorigenicity in HCC 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deacetylation is mediated by histone deacetylase (HDAC), which catalyzes the removal of acetyl functional group from the N‐terminal tails of histone proteins, resulting in a more compact chromatin structure and represses gene transcription. Previous studies have indicated that the higher expression of HDACs is associated with tumor cell proliferation, differentiation, invasion, and metastasis and is highly correlated to poor prognosis and survival rate 4,5 . HDACs are involved in gene regulations, stress resistance, and tumorigenicity in HCC 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Apicidin, a novel class of HDAC inhibitor derived from a fungal metabolite, 7 is involved in regulating the HAC process by affecting the balance between histone acetyltransferases and HDACs. Previous studies have reported that apicidin is effective against various cancer cell lines because of its potent antiproliferative property; thus, it is considered a potential anticancer therapeutic agent 4,5 . Moreover, the combination of apicidin with other anticancer drugs, such as doxorubicin, increases the antitumor effects of doxorubicin via induction of apoptosis‐related proteins and cell growth inhibition in HCC 8 …”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] It has been reported to have a potent broad spectrum of antiproliferative activities against various cancer cell lines. [47][48][49] The combination of apicidin with doxorubicin enhances the antitumor effect of doxorubicin on caspase activation and tumor growth in HCCs, 50) but, the growth-inhibitory concentrations of apicidin in HCCs were higher than MCF-7 breast, AGS gastric and HepG2 liver cancer cell lines. 19,20) Thus, induction of side effects and chemoresistance by apicidin can be expected for HCCs treatment.…”
Section: )mentioning
confidence: 99%